Design and statistical optimization of an effervescent floating drug delivery system of theophylline using response surface methodology - Srikanth Meka, Venkata; Ee Li, Chew; Sheshala, Ravi (Acta Pharmaceutica, 2016)
The aim of this research was to formulate effervescent floating drug delivery systems of theophylline using different release retarding polymers such as ethyl cellulose, Eudragit L100, xanthan gum and polyethylene oxide (PEO) N12K. Sodium bicarbonate was used as a gas generating agent. Direct compression was used to formulate floating tablets and the tablets were evaluated for their physicochemical and dissolution characteristics. PEO based formulations produced better drug release properties than other formulations. Hence, it was further optimized by central composite design. Further subjects of research were the effect of formulation variables on floating lag time and the percentage of drug released at the seventh hour ( ). The optimum quantities of PEO and sodium bicarbonate, which had the highest desirability close to 1.0, were chosen as the statistically optimized formulation. No interaction was found between theophylline and PEO by Fourier Transformation Infrared spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC) studies.